Validation of PROMIS Profile‐29 in adults with hemophilia in the Netherlands. (3rd August 2021) - van Balen, Erna C.; Haverman, Lotte; Hassan, Shermarke; Taal, Elisabeth M.; Smit, Cees; Driessens, Mariëtte H.; Beckers, Erik A. M.; Coppens, Michiel; Eikenboom, Jeroen; Hooimeijer, Hélène L.; Leebeek, Frank W. G.; van Vulpen, Lize F. D.; et al.
Abstract: Background: The Patient‐Reported Outcomes Measurement Information System (PROMIS) Profile‐29 questionnaire is widely used worldwide, but it has not yet been validated in the Netherlands, nor in persons with hemophilia. Objective: To validate the Dutch‐Flemish version of the PROMIS‐29 Profile v2.01 in adults with hemophilia. Methods: Dutch males with hemophilia (all severities) completed questionnaires that contained sociodemographic and clinical characteristics, the PROMIS‐29, RAND‐36, and the Hemophilia Activities List (HAL). Structural validity of each subscale was assessed with confirmatory factor analysis (CFA). Internal consistency was calculated for each subscale with sufficient model fit in CFA. Construct validity was assessed by testing hypotheses about (1) correlations of each PROMIS‐29 subscale with corresponding scales of RAND‐36 and domains of HAL, and (2) mean differences in T ‐scores between subgroups with different hemophilia severities, self‐reported joint impairment, and HIV infection status. We considered ≥75% of data in accordance with the hypotheses evidence for construct validity. Results: In total, 770 persons with hemophilia participated in this cross‐sectional study. CFA revealed sufficient structural validity for five subscales: Physical Function, Depression, Sleep Disturbance, Ability to Participate in Social Roles and Activities, and Pain Interference. Internal consistency was high and Cronbach's alpha ranged from 0.79 for Sleep Disturbance to 0.96 for Pain Interference. Differences between clinical subgroups were in the expected direction. Construct validity was confirmed for Physical Function, Anxiety, Depression, Fatigue, Sleep Disturbance, and Pain Intensity. Conclusion: This study revealed sufficient evidence for structural validity, internal consistency, and construct validity for most PROMIS Profile‐29 subscales among people with hemophilia in the Netherlands.